Research Progress in Mechanisms of Drug-Resistance of Macrolide Antibiotics Resistance in Mycoplasma pneumoniae - Meixuan Jia
This review aims to enhance understanding of Mycoplasma pneumoniae (MP) infection and Macrolide-Resistant Mycoplasma pneumoniae (MRMP) pneumonia, emphasizing their epidemiological characteristics and resistance mechanisms. MP is a major cause of Community-Acquired Pneumonia (CAP) in children, with potential extra-pulmonary manifestations. The objective is to guide early diagnosis and timely treatment, addressing the challenges posed by MP$1 (Bs resistance to gb(B-Lactam and vancomycin drugs.s